Employability as a New Mission:Organizational Changes in Chinese Higher Vocational Colleges - Po, Y.; Lin, X. Y. (Research in Educational Development, 2012)
The analysis is based a multiple-case study.The analytical framework is developed from sociology theories and organizational theories.This study argues that vocational colleges in China have been experiencing substantial transformations.At the macro-level,influenced by the neo-liberal arguments for globalization,they have been transforming from social institutions to industries,with cultivating employability as their new mission.At the micro-level,under the influence of the new mission,there have been considerable changes in program goal,program development,curriculum development,dominant pedagogy,faculty development,and internal management.These changes fit the rhetoric of the employability as core competency,as well as the impact-reaction model for organizational change.The implication of these changes is that Chinese vocational higher education institutions may be degenerated to employment training organizations.
Keywords: employability; vocational college; institutional mission